The Effectiveness of Online Problem-Based Learning in Improving Students' Reading Comprehension with Different Learning Styles - Muriyah Muriyah; Sri Wahyuni; Mursid Saleh (English Education Journal, 2023)
Reading is a fundamental skill for conveying information. Nowadays, various information is easily accessible quickly from many sources worldwide, so reading comprehension skills and mastering technology have been crucial for the challenges. Educators need a strategy to improve these skills. This study aims to measure the effectiveness of Problem-Based Learning through Google Classroom in improving the reading comprehension of students with different learning styles. This study used a quasi-experimental with a 2Ã—4 factorial design on the tenth-grade students at SMAN 1 Sindang, Indramayu. The VARK questionnaire and reading comprehension test were carried out by one-sample Kolmogorov-Smirnov test and two-way ANOVA with Tukey's. The study exposed the result of Problem-Based Learning through Google Classroom and the influence of the student's different learning styles on the reading comprehension learning outcomes. This research indicated that the strategy was effective, but the student's different learning styles did not affect their learning outcome. Thus, there was no interaction between the teaching strategy and students' learning styles in improving their reading comprehension learning outcomes. This study offered a new perception of the importance of considering student's learning styles in organizing the appropriate materials, learning activities, and assessments to improve reading comprehension. The contribution of this study to the ELT in advance was a new awareness of the effectiveness of multi-mode digital settings in fulfilling the student's needs. Thus, it is confirmed that recent education is designed to accommodate students anywhere and anytime.